Psychological and pedagogical aspects of objectivity in assessing productive speech activities in large-scale standardized testing - Boichuk, Iryna Vasylivna (Global Prosperity, 2025)
The study introduces a customized methodological model for evaluating the professional effectiveness of foreign language teachers. The model is connected to the dynamics of students’ academic achievement and teachers’ professional effectiveness. The findings from the literature review and presented in the paper support the notion that Value-Added Modeling (VAM) combined with communicative-oriented assessment practice forms a valid, rigorous, and context-sensitive method of measuring teacher results. Research evidence supports this fact, as standardized examination scores increased from 156 to 178 points. This is evidence that communicative and formative assessment strategies may not only lead to improved academic performance, but also greater consistency in learning outcomes. Through blending quantitative elements of student progress with qualitative aspects of instructional practice, the suggested model overcomes the main constraints in conventional approaches to evaluation. It also conforms to current models of instructional practice rooted in competency-based and data-driven teaching and learning. This paradigm-making process has implications for policymakers and schools that want to better account for their policies that affect accountability, transparency, and instructional quality in the context of ongoing educational reforms. In conclusion, the research enhances the literature on teacher effectiveness and is theoretically and methodologically relevant to teachers; and lays the groundwork for further refinement and application of VAM-based approaches to teaching in a variety of contexts. The proposed framework may also serve as a methodological basis for improving examiner training and strengthening quality assurance in large-scale language assessment. In this regard, the study highlights practical pathways for enhancing fairness and consistency in productive speech evaluation without diminishing the professional role of expert raters.